Relationship Between Nutrition Status, Growth And Development For Children Aged 15 Years At Railaco Health Center, Ermera Municipality, Timor-Leste 2023 - de Deus, Elisa; da Costa Guterres, Ana Claudia; Santos Ximenes, Rafael dos; Boavida Tilman, Carlos; Jesus Vaz Cabral , Teresa de; de Jesus, Acacio (CV RIFAINSTITUT, 2024)
1-5 year children as an investiment for a nation, because they are the new generations for a nation. The quality of the nation in the hands of infants because the infants as a human resource that harm now implements with the systematic and continues to increase growth and development for infants in pre-school ages to be optimal through the state of nutrition with quality and certain (Judanwanto, 2019). This research wanted to identify a relationship between the nutrition state and the development growth for children in the preschool period in Health Center Railaco, Ermera municipality, Timor-Leste. To identify a relationship between nutritional state and growth and development for children in the pre-school period in Health Center Railaco, Ermera municipality, Timor-Leste. in this research they use the quantitative method in the approach with cross sectional approach in the techical use of non probability sampling with the type of accidental sampling. the result of research for 65,8% of children with moderate nutritional status and 34,2% good. And there is 59,1% moderate growth and 40,9% are good. And there is 63,8% moderate development and 36,2% are good. The result of the statistic using the Chi Square test between the nutritional status and the growth and development, it identifies p value= 0,000 0r p=< 0,05